2002
DOI: 10.1111/j.1741-4520.2002.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a transposon into the Gli3 gene in the Pdn mouse

Abstract: The phenotype of the genetic polydactyly/ arhinencephaly mouse (Pdn/Pdn) is similar to Greig cephalopolysyndactyly syndrome (GCPS), whose responsible gene is GLI3. Suppression of Gli3 gene expression has been observed in the Pdn/Pdn and integration of retrotransposon in Gli3 gene in the Pdn mouse has been reported. Thus, the responsible gene for Pdn/Pdn is thought to be Gli3, but the site of mutation within the gene has not been demarcated. In the present study, we demonstrated that 5442 bp of early retrotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 28 publications
(30 reference statements)
2
29
0
Order By: Relevance
“…This analysis also revealed low amounts of an additional Pdn/Pdn-specific Gli3 protein of ϳ85 kDa (Fig. 1 I, asterisk), which is likely to be encoded by previously described alternative splice products, leading to the insertion of 56 or 61 aa in the N-terminal part of the Gli3 protein (Thien and Rüther, 1999;Ueta et al, 2002). The presence of a Gli3 activator protein containing the same additional amino acids is likely, but could not be resolved on these gels due to its high molecular weight (170 kDa compared with 175 kDa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis also revealed low amounts of an additional Pdn/Pdn-specific Gli3 protein of ϳ85 kDa (Fig. 1 I, asterisk), which is likely to be encoded by previously described alternative splice products, leading to the insertion of 56 or 61 aa in the N-terminal part of the Gli3 protein (Thien and Rüther, 1999;Ueta et al, 2002). The presence of a Gli3 activator protein containing the same additional amino acids is likely, but could not be resolved on these gels due to its high molecular weight (170 kDa compared with 175 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…Embryonic (E) day 0.5 was assumed to start at midday of the day of vaginal plug discovery. Embryos were genotyped as described previously (Ueta et al, 2002). In qualitative analyses of mutant phenotypes, heterozygous and wildtype embryos did not show differences and both were used as control embryos.…”
Section: Methodsmentioning
confidence: 99%
“…Gli3 is the responsible gene for the Pdn mouse (Thien & Rüther 1999; Naruse et al . 2000, 2001; Ueta et al . 2002) and GLI3 for GCPS (Vortkamp et al .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Pdn/Pdn mice do not seem to have any thumbs/big toes because neither factor is found in the fore/hindlimbs of Pdn/Pdn mice. In the molecular study, Ueta et al (2002) observed the suppression of Gli3 gene expression in Pdn mice and considered Gli3 to be the gene responsible for Pdn/Pdn mutant mice. According to Lallemand et al (2005), Msx1 and Msx2 are highly expressed in early limb formation, and anterior skeletal elements, such as thumb/hallux and radius/tibia, are lacking in Msx1 and Msx2 doublemutant mice.…”
Section: Discussionmentioning
confidence: 99%